Morphological and Spectroscopic Characterization of Costus afer Ker Gawl. Leaf on Surface Modification with Archachatina marginata Mucus as a Potential Carrier for Anti-diabetic Therapy - Matthew Onyema, Agu; Yakubu, Shedrach; Cletus, Ukwubile; Chibuike Sylvester, Onyima; Chibuzor Odidika, Collins; Chinedu Jude, Onwuka (Science Tech Group, 2025)
FTIR and SEM analyses were conducted on Costus afer Methanol leaf extract (CAPExt), Snail mucus (GALSM), and a mixture of extracts to study surface modification of snail mucus. The FTIR of the plant extract and mixed extracts [CAPExt/GALSM] showed strong absorption bands. The absorption bands at 3363.97 – 3363.25, 2854.74 – 2962.74, 1381.08 – 1450.52, 1519.96 – 1558.54, 1651.12 – 1712.85, 1242.20 – 1265.35, and 1033.88 – 1165.04 cm-1 were characteristic absorption peaks of O – H stretching vibrations, C – H deformation, aromatic rings, esters, acetyl groups, and carboxylate groups. SEM images reveal a smooth plant extract surface with a rough area containing bioactive molecules, while snail mucus morphology reveals crystalline cube-shaped molecules. SEM images reveal rocky, swollen, roughened, and bulging CAPExt/GALSM molecules, suggesting a new method for structural development of anti-diabetic drug carriers, potentially releasing plant material intermittently upon absorption.